Prototipe Aplikasi Kelas Pintar (SmartClass) Dengan Konsep Internet Of Thing (IOT) menggunakan Arduino - Romi Hendri; Khozainuz Zuhri; Nugroho Yulianto (Universitas Mitra Indonesia, 2020)
AbstractAlong with the times, the remote control system uses android. The disorderly use of facilities and the spread of the Covid-19 Virus about the government's appeal not to touch objects carelessly. Smartclass is a class facility control system using Arduino Uno + ESP8266 as a device control unit, Firebase as a Database Server, and Kodular to create android applications. Smartclass is a system that provides automation of class usage so that classes can be controlled via Android and users don't have to press a switch. The integration between schedule and class usage makes this system run automatically. The results showed that the Android-based application system can be controlled well, the system does not have a difference between the time of the tool and the actual clock as proven by testing the comparison of the RTC time with the stopwatch, the pir sensor is able to detect ± 5.4 meters movement. If the object is not moving, the pear sensor cannot detect an object so that the control application system can run properly.